Electropolishing of surfaces: theory and applications - Yang, G.; Wang, B.; Tawfiq, K.; Wei, H.; Zhou, S.; Chen, G. (Surface engineering, 2017)
Electropolishing is the electrochemical process to remove the metallic material from the workpiece, in order to obtain a smoother metal surface. It has found vast engineering applications in many fields, such as food, medical, pharmaceutical and semiconductor industries. This review is aimed to provide the readership with insightful understanding of the electropolishing process, from the fundamental aspects as well as from the application aspects. The general aspects of electropolishing, including its definition, the classic setup, the fundamentals behind it and methods used to evaluate the electropolishing finishes are reviewed here. Various electropolishing theories, be them quantitative or qualitative are briefly discussed. Based on those theories, important parameters evolved in the electropolishing process are enumerated. Many microscopic technologies are used to evaluate the electropolishing surface finishes. This includes optical microscope, electron microscope and atomic force microscope. Some key features of electropolishing are briefly outlined in the end.